«Лісова пісня» Лесі Українки: міфологія поліського пограниччя в перегуках з творчістю А. Міцкевича та у музичних інтерпретаціях - Драганчук-Кашаюк, Вікторія Миколаївна (Państwowa Wyższa Szkoła Zawodowa im. Jana Grodka w Sanoku, 2018)
The reasons of Polesye mythology in the ballads „Svityazyankaˮ and „Fishˮ by А. Mitskevich and drama-fairy „The Forest Songˮ by Lesya Ukrainka are compared in the article. The analysis of musical interpretations features of this phenomenon in M. Skorulskyi’s ballet, V. Kyreyko’s opera, in music to the movies by I. Shamo and Y. Stankovych is carried out. The interpretation of forest beautiful woman Mavka’s character and her love with a rural fellow Lukast through the Volyn Polesye folklore melodies in sopilka’s sounding that was offered to the drama-fairy by Lesya Ukrainka is accented in the article.
Keywords: творчість Лесі Українки в музиці; українська і польська культура пограниччя; "Лісова пісня"; музична інтерпретація